Mechanisms of Coordinated Distribution of the Effect from Export/Import Transactions - Geraskin, M. I.; Ajupov, A. A.; Kurilova, A. A. (International Journal of Economics and Financial Issues, 2016)
Economic mathematical model for coordinating economic interests of the regions (companies) and state budgets within the system of export/import transactions is developed. Nash equilibrium mechanisms for hierarchical and nonhierarchical coordination of effect distribution and mechanism of comprehensive coordination of export/import indicators are presented. The author has developed a two-sector model of export/import transactions and the optimal mechanisms for it. There has been carried out a simulation of coordination mechanisms for crude oil (Russia) and oil extraction equipment (Germany). Keywords: export, import, coordination model, effect distribution mechanism, hierarchical system, nonhierarchical system, Nash equilibrium. JEL Classifications: O150; E660; R130